(untitled) (CIPEEX, 2022)
THE PRESENT WORK AIMS TO DEVELOP AN EMBRICATION ABOUT THE WORKS OF CAROLINA MARIA DE JESUS AND THE ARTICLES OF REFLECTIONS, ANALYZES AND SOCIAL RIGHTS, FROM THE SOCIAL LEGAL POINT OF VIEW. IT SHOULD ALSO ANSWER THE FOLLOWING QUESTION: "WERE CAROLINA MARIA DE JESUS’ SOCIAL RIGHTS VIOLATED?". IN ADDITION TO REFLECTING ON THE THEORETICAL BASES OF SOCIAL RIGHTS, AS WELL AS UNDERSTANDING HOW SOCIAL RIGHTS ARE STRUCTURED IN THE FEDERAL CONSTITUTION AND UNDERSTANDING HOW THE ISSUE OF SOCIAL RIGHTS AS FUNDAMENTAL RIGHTS WORKS IN THE WORK OF CAROLINA MARIA DE JESUS.